Broadband extended cantilever model for magnetic component windings. - Ngo, K.D.T (IEEE Transactions on power electronics)
The extended cantilever model is modified to enable broadband representation of multiple magnetic windings using s-domain transfer functions. A linear formulation for extracting the parameters is proposed in which the current-sense impedances do not have to be assumed negligible. The model has been implemented in a circuit simulator that supports transfer function blocks. It has been verified experimentally using a five-winding power transformer. The experimental transformer is simulated embedded in a two-transistor forward converter to examine simulation speed and convergence issues